(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Since the beginning of the 1990s the nano-lipid carriers (NLCs) have been attracting a growing interest from the pharmaceutical technology research groups worldwide. NLCs appeared as consumer products first on the cosmetic market. The article gives an overview of the cosmetic benefits including enhancement of chemical stability of actives, film formation, controlled occlusion, skin hydration, skin bioavailability, and physical stability of the lipid nanoparticles. Solid-lipid nanoparticle as topical formulations. List of the cosmetic products currently available in the market, and bioequivalence protocol, excipients, improvement of the benefit/risk ratio of the topical therapy is shown.